2023
DOI: 10.1038/s41598-023-30042-y
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating the wave power-salt marsh retreat relationship

Abstract: Salt marshes are threatened by rising sea levels and human activities, and a major mechanism of marsh loss is edge retreat or erosion. To understand and predict loss in these valuable ecosystems, studies have related erosion to marsh hydrodynamics and wave characteristics such as wave power. Across global studies, erosion is reported to be largely linearly related to wave power, with this relationship having implications for the resilience of marshes to extreme events such as storms. However, there is signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Wave power has generally been related to marsh lateral erosion (e.g., Houttuijn Bloemendaal et al., 2023; Leonardi et al., 2016; McLoughlin et al., 2015). Waves can deepen tidal flats facing marsh edges and consequently enhance wave energy (Fagherazzi et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Wave power has generally been related to marsh lateral erosion (e.g., Houttuijn Bloemendaal et al., 2023; Leonardi et al., 2016; McLoughlin et al., 2015). Waves can deepen tidal flats facing marsh edges and consequently enhance wave energy (Fagherazzi et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, however, a wide range of field-based studies have identified a nonlinear fit between lateral erosion and wave power, with x = 1.10 to 1.37, e.g., (5)(6)(7)(8)(9)(10). These studies have shown a large amount of variability in erosion across field sites, caused by differences in soil properties, vegetation, and myriad other factors (11). While these inherent differences among the sites can be partially accounted for by standardizing the individual erosion measurements by the mean quantity of erosion at each site (12), nonwave erosive effects still contaminate the field datasets and raise the exponent x.…”
Section: Introductionmentioning
confidence: 99%
“…While these inherent differences among the sites can be partially accounted for by standardizing the individual erosion measurements by the mean quantity of erosion at each site (12), nonwave erosive effects still contaminate the field datasets and raise the exponent x. For example, mass wasting driven by gravity (13), tidal creek flows (14)(15), alongshore current velocity-driven erosion (11,16), precipitation-driven erosion (17), and soil cracking due to wetting and drying effects (18) each occur at different frequencies across time (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although physical factors like wind action, wave energy, and tides contribute significantly to marsh erosion rates [16,17], biological factors interacting with these physical forces also play an important role in geomorphological processes. Autogenic ecosystem engineers and allogenic ecosystem engineers, along with herbivores and their predators, influence primary production and the stability of these environments [4,[18][19][20][21]. Invasive species further complicate ecological systems by altering the evolutionary pathways of native species, modifying the structure of biological communities, and disrupting habitat complexity [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%